The Effectiveness of Different Baits on Collapsible Trap to Catch Swimming Crab Based in Archipelagic Fishing Port of Karangantu - Niken Widowati; Ririn Irnawati; Adi Susanto (Jurnal Perikanan dan Kelautan, 2015)
The Archipelagic Fishing Port of Karangantu is one of the central swimming crabs fishing in Banten Province. Traps is passive fishing gear that usually use bait to attract swimming crabs or other fish. The goals of this research are to analyze the influence of baits and it’s effectiveness to catch swimming crabs using collapsible trap. The research was conducted with experimental fishing using fresh common ponyfish, salted common ponyfish and fish offal as baits. This study was conducted at 20th January-11th April 2015. Data analyzed using a completely randomized design. The results show that the types of bait have significant effect to number and weight of swimming crabs into traps. Fresh common ponyfish baits have significant effect then other baits because it have high protein that which can produce odors to attract swimming crabs into come to traps.